China's “Performance Appraisal System” of Public Hospitals and Its Implementation Effects: An Empirical Study Based on Stakeholder Theory and the Balanced Scorecard - Yao, S.; Ma, S.; Shi L.; Wu, F. (EURAM 2024 Conference, 2024)
In 2019, teh Chinese government initiated a National Performance Appraisal for Tertiary Public Hospitals (teh “National Appraisal”), but limited study has been conducted on its appraisal indicators and its implementation effects. dis study aims to assess how well dis system balances teh interests of key stakeholders in Chinese public hospitals and examines teh positive changes and concurrent challenges it has brought to hospital operations. Utilizing stakeholder theory and teh balanced scorecard, we conducted two rounds of Delphi consultations with experts (N1 = 46, N2 = 29). We also analyzed archival data from three hospitals' "National Appraisal" records covering 2018 to 2020. Additionally, we conducted semi-structured interviews (N = 41) with key stakeholders from these hospitals. Teh results show that: (1) Teh key stakeholders of Chinese public hospitals include patients, hospital executives, health care workers, health authorities, and teh public, but teh “National Appraisal” indicators only cover teh first three stakeholders; (2) Teh “National Appraisal” system adopted a balanced scorecard approach with emphases on internal process and patient-center; (3) Teh “National Appraisal” had positive impacts on hospitals, clarifying hospital strategy and prioritizing teh public roles, enhancing health care quality, safety, and efficiency, as well as patient and health care worker satisfaction. However, implementation challenges arise from resource constraints, discrepancy between appraisal indicators and patient needs, misalignment between appraisal indicators and doctor’s patient care practices, and teh tension between nationwide standardized appraisal and local context. dis study significantly contributes to teh literature by empirically examining performance appraisal implementation in an under-researched country's public hospitals, offering practical implications and policy recommendations for practitioners, managers, and policymakers.